AIDS Cholangiopathy Secondary to Cytomegalovirus as Possible Unmasking Immune Reconstitution Inflammatory Syndrome in Human Immunodeficiency Virus-Infected Individual: Case Report and Review of the Literature - Moiz Topiwala; Nachiket Dubale; Mahender K. Medisetty; Sunil Gaikwad; Divya Patel; Sanjay Pujari (Case Reports in Infectious Diseases)
We present the first case report of cytomegalovirus (CMV) cholangiopathy as possible immune reconstitution inflammatory syndrome (IRIS) in a human immunodeficiency virus (HIV)-infected individual, within two months of starting effective HAART. The patient presented with abdominal pain, nausea, vomiting, decreased appetite, and jaundice. The patient was diagnosed on ERCP as AIDS cholangiopathy, and biopsy of the ampulla showed acute inflammation with CMV inclusion bodies. The patient underwent sphincterotomy with CBD stenting and HAART continued without use of ganciclovir or valganciclovir. On follow-up, the patient achieved clinical and histopathological cure, which was demonstrated on repeat ampullary biopsy.